Plz help... e^(3x) = 10^(2x) * 2^(1-x)
B botley111222 New member Joined Jul 29, 2010 Messages 3 Jul 29, 2010 #1 Plz help... e^(3x) = 10^(2x) * 2^(1-x)
mmm4444bot Super Moderator Joined Oct 6, 2005 Messages 10,962 Jul 29, 2010 #2 Raise each side of the equation to the power of 1/x. Then, taking the natural logarithm on both sides and simplifying leads to the following equation. (1 - x)/x = [3 - 2*ln(10)]/ln(2)
Raise each side of the equation to the power of 1/x. Then, taking the natural logarithm on both sides and simplifying leads to the following equation. (1 - x)/x = [3 - 2*ln(10)]/ln(2)
S soroban Elite Member Joined Jan 28, 2005 Messages 5,586 Jul 29, 2010 #3 Hello, botley111222! \(\displaystyle \text{Solve for }x\!:\;\; e^{3x} \;=\; 10^{2x}\cdot 2^{1-x}\) Click to expand... \(\displaystyle \text{Take logs: }\qquad \ln\left(e^{3x}\right) \;=\;\ln\left(10^{2x}\cdot2^{1-x}\right)\) . . . . . . . . . . . .\(\displaystyle 3x\ln e \;=\;\ln\left(10^{2x}\right) + \ln\left(2^{1-x}\right)\) . . . . . . . . . . . . \(\displaystyle 3x\cdot 1 \;=\;2x\ln 10 + (1-x)\ln2\) . . . . . . . . . . . . . . \(\displaystyle 3x \;=\;2x\ln10 + \ln 2 - x\ln 2\) . . .\(\displaystyle 3x - 2x\ln10 + x\ln2 \;=\;\ln 2\) . . . \(\displaystyle x(3 - 2\ln10 + \ln2) \;=\;\ln2\) . . . . . . . . . . . . . . .\(\displaystyle x \;=\;\frac{\ln 2}{3 - 2\ln10 + \ln2}\) Edit: corrected one of my favorite typos . . . z instead of x. .
Hello, botley111222! \(\displaystyle \text{Solve for }x\!:\;\; e^{3x} \;=\; 10^{2x}\cdot 2^{1-x}\) Click to expand... \(\displaystyle \text{Take logs: }\qquad \ln\left(e^{3x}\right) \;=\;\ln\left(10^{2x}\cdot2^{1-x}\right)\) . . . . . . . . . . . .\(\displaystyle 3x\ln e \;=\;\ln\left(10^{2x}\right) + \ln\left(2^{1-x}\right)\) . . . . . . . . . . . . \(\displaystyle 3x\cdot 1 \;=\;2x\ln 10 + (1-x)\ln2\) . . . . . . . . . . . . . . \(\displaystyle 3x \;=\;2x\ln10 + \ln 2 - x\ln 2\) . . .\(\displaystyle 3x - 2x\ln10 + x\ln2 \;=\;\ln 2\) . . . \(\displaystyle x(3 - 2\ln10 + \ln2) \;=\;\ln2\) . . . . . . . . . . . . . . .\(\displaystyle x \;=\;\frac{\ln 2}{3 - 2\ln10 + \ln2}\) Edit: corrected one of my favorite typos . . . z instead of x. .
mmm4444bot Super Moderator Joined Oct 6, 2005 Messages 10,962 Jul 29, 2010 #4 Since Soroban finished the exercise, I will post my solution, too (which is equivalent). x = ln(2)/[3 - ln(50)]
Since Soroban finished the exercise, I will post my solution, too (which is equivalent). x = ln(2)/[3 - ln(50)]